CHRISTIAN THINKERS ON INTERNATIONAL RELATIONS (REINHOLD NIEBUHR AND GIORGIO LA PIRA) - T. V. Zonova (Vestnik MGIMO-Universiteta)
The author examines the legacy of two great Christian thinkers, the American Reinhold Niebuhr and the Italian Giorgio La Pira. Reinhold Niebuhr was a protestant theologian and political adviser to the Council of Foreign Relations and George Kennan’s Policy Planning Staff. The Mayor of Florence, Giorgio La Pira was a Dominican tertiary and professor of Roman law; he was a prominent Italian statesman and one of the fathers of the Italian Constitution. During the Cold War period both played a significant role in influencing public opinion, both proved to be among most influential religious thinkers of the 20th century. The author analyzes their views on international relations, in particularly on the western policy towards the Soviet Union, the use of nuclear weapons, the war in Vietnam and the communist issue. The legacy of the two thinkers is highly topical in front of the ethical dimension of choices in international politics today. Therefore the names of Christian thinkers are back again to the fore. It is worth noting that President Obama cites Niebuhr as one of his favorite philosophers. In an interview with «The New York Times» Obama felt it necessary to emphasize the Niebuhr's idea that there is “a real evil, fatigue and pain in the world, and one should be careful and modest in his belief of being able to eliminate these things. Nevertheless, we should not use it as an excuse for cynicism and inaction”. European observers and scholars also admit that Obama is following the thought of Niebuhr, who was demythologizing the idea of America as a visible place of the Kingdom of God». Niebuhr was well aware of the limitations of all humane schemes. Giorgio La Pira was aware as well that politics should always base on ethical principles and reflect the existing spiritual, cultural, political and economic diversity. His main purpose was the formation of a new hierarchy of values. Just like Reinhold Niebuhr, Giorgio La Pira, reflecting on key events of the 20th century, looked for a policy based on the precepts of Christianity. Just like Reinhold Niebuhr, La Pira stated the primacy of politics over economics. However there were some differences between the two thinkers. Niebuhr’s ontological pessimism was well known. On the contrary, La Pira was an optimist. He sincerely believed that his personal policy would help mankind to promote the cause of a new world.